IN VITRO EVALUATION OF THE INTERACTIONS BETWEEN CRUDE LEAF EXTRACTS OF HELICHRYSUM PEDUNCULATUM AND SOME ANTIBIOTICS - Aiyegoro, O. A.; Afolayan, A. J.; Okoh, A. I. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The effect of combinations of the crude acetone, methanol and water extracts of Helichrysum pedunculatum leaves and eight first-line antibiotics was investigated by means of fractional inhibitory concentration (FIC) indices as well as by the use of time kill assays. Using the FIC indices synergistic interactions were observed on most of the bacteria tested and this is independent of Gram reaction characteristics (FIC indices of ≤ 0.875) with combinations in the aqueous extract yielding largely antagonistic interactions (FIC indices of ≥ 2.0). The time kill assay detected synergy that is also independent of Gram reaction characteristics with a ≥ 1000 times (≥ 3Log10) potentiation of the bactericidal activity of tetracycline and ciprofloxacin against Klebsiella pneumoniae as well as that of penicillin G and oxytetracycline against Proteus vulgaris. We conclude that acetone and methanol extracts of H. pedunculatum could be potential sources of broad spectrum antibiotics resistance modifying compounds.